Effectiveness of the System and Procedures for Fixed Asset Accounting Management at the Regional Financial Agency of Depok City - Intan Kusumawardany; Petrolis Nusa Perdana; Hafifah Nasution (Journal of Business Innovation and Accounting Research, 2025)
Intan Kusumawardany. Effectiveness of the System and Procedures for Fixed Asset Accounting Management at the Regional Financial Agency of Depok City. Undergraduate Thesis, Faculty of Economics, Universitas Negeri Jakarta, 2024. This study aims to analyze the effectiveness of asset management and the accounting treatment of fixed assets at the Regional Financial Agency (Badan Keuangan Daerah/BKD) of Depok City. The effectiveness analysis evaluated whether the fixed asset management systems and procedures implemented by BKD Depok City comply with the Regulation of the Minister of Home Affairs (Permendagri) No. 19 of 2016 concerning Guidelines for the Management of Regional Property (Barang Milik Daerah/BMD). Meanwhile, the analysis of accounting treatment was carried out by examining the fixed asset accounting practices applied in the financial reporting of BKD Depok City and assessing their conformity with Government Accounting Standard Statement (PSAP) No. 07 of 2010. This research uses BKD Depok City as the object of study. BKD Depok City is a Regional Government Work Unit (SKPD) under the Government of Depok City. The study employs a descriptive qualitative research method using both primary and secondary data sources. Data analysis was conducted through content analysis. The findings indicate that the asset management effectiveness score for BKD Depok City was 73%, placing it in the “moderately effective” category. This means that BKD Depok City has implemented regional asset management based on Permendagri No. 19 of 2016; however, out of eleven indicators examined, only eight indicators have been fully implemented. The three indicators that have not been fulfilled include needs planning and budgeting, utilization, and safeguarding of regional property. Meanwhile, the analysis of fixed asset accounting treatment shows that BKD Depok City has implemented accounting practices that are fully consistent with PSAP No. 07 of 2010. This study recommends that BKD Depok City follow up on the asset management indicators that are not yet aligned with Permendagri No. 19 of 2016, while maintaining compliance with PSAP No. 07 of 2010 in the accounting treatment of fixed assets and continuously updating relevant policies.